Tracing the genetic origin of african descendants from South America - (:unkn) unknown (My University, 2015)
Background The transatlantic slave trade, from the 15th to the 19th centuries, changed dramatically the demography of the Americas. Thousands of enslaved Africans managed to escape from the plantations of European colonizers, and formed independent African settlements of free people (or 'Marron'). Here, we study four Noir Marron communities from French Guiana and Surinam, as well as other populations with noteworthy African heritage in Brazil and Colombia, and West African populations in Benin, Ivory Coast, and Mali. To uncover different population histories, these populations were specifically characterized using different genetic markers based on 17 Y-STRs, 96 Y-SNPs, whole mtDNA genome, and genome-wide SNP data (4.5 million autosomal SNP). Results Paternally and maternally inherited DNA highlighted different patterns of sex-biased gene flow in both Afro-Brazilian and Afro-Colombian populations that suggest different preferential marriage behaviours. In sharp contrast, the Noir Marron communities presented the highest African ancestry in all genetic systems analysed (above 98%). These communities have apparently a null gene flow with non-African groups, and also present elevated inbreeding coefficients. In good agreement with linguistic studies, the Noir Marron communities showed a biogeographical ancestry associated with historical West African Kingdoms that existed in modern Benin during the slave trade. Afro-Colombians indicated genetic ancestry linked with the Gold Coast region. While Afro-Brazilian genetic ancestry was linked with the West Central African region, also supported by historical research. Conclusions This study provides specific genetic information in African Americans and thereby helps us to reconstruct broken links with their African past. The Noir Marron communities revealed a remarkably high African identity, which is still linked to Bight of Benin region. The Afro-Brazilian and Afro-Colombian populations present different demog
Keywords: African Research